Efeito dos ciclos térmicos da manufatura aditiva por soldagem a arco sobre a dureza e microestrutura da zac de um ferro fundido nodular - Ferraresi, Henrique Nardon (2018)
In the automotive sector, molds and dies for sheet forming have been manufactured in cast iron, economically replacing tool steel, which present higher costs for machining. The change in the design of these matrices, due to the launch of new products, implies the premature replacement of these tools. However, the manufacturing of a new matrix by casting has high costs and long lead times. One solution would be to manufacture cast iron molds in a custom way, but without the need for molding or machining from a block. The Arc Welding Additive Manufacturing (MASA) with the GMAW (Gas Metal Arc Welding) process is a promising technique for this type of customization. The MASA consists of the manufacture of metal preforms from the deposition of multilayer of weld beads on a substrate. One of the great challenges of MASA for casting molds and die cast irons is related to the formation of a high hardness microstructure in the region of the Heat Affected Zone (HAZ) and in the Partially-Melted Zone (PMZ) during welding. These fragile regions, together with the contraction tensions, can lead to the formation of cracks in the matrix application. In this sense, the present work has as objective to determine the effects of the thermal cycle of the MASA-GMAW on the hardness of HAZ and PMZ of a nodular cast iron substrate, from the application of buttery layers. To achieve this goal, 5 layers of buttery were staggered and the respective thermal welding cycles were acquired by inserting a thermocouple into the substrate. In this step, the microstructural and microhardness transformations that occurred in the HAZ and PMZ of the 1st Layer were analyzed systematically due to the subsequent layers (2nd, 3rd, 4th and 5th). With the actual welding thermal cycles it was possible to perform physical simulations through a HAZ simulator. It was concluded through the actual welding and the simulations that the subsequent layers of weld cause the ZAC tempering of the cast iron. Through the simulation, it was also possible to control the microhardness and the final microstructure type of the HAZ through the preheating, intercalation and post-heating temperature. Finally, the validation of the study occurred through the construction of a folded matrix in reduced dimensions and the submission of the same to work. The results showed that the use of MASA-GMAW for the customization of a nodular cast iron matrix is adequate and promising.